Desmoplastic Small Round Cell Tumor, a “Floating Island” Pattern in Pleural Fluid Cytology: A Case Report and Review of the Literature - Hui Zhu; Emily Marie McMeekin; Charles D. Sturgis (Case Reports in Pathology)
Desmoplastic small round cell tumor (DSRCT) is a rare aggressive sarcoma with characteristic clinical and pathologic features. It typically involves pelvic and abdominal organs of young male patients, and patients usually present at advanced stage with poor prognosis. A few reports are available describing the cytopathologic features of DSRCT in serous effusions, with the majority of published cases depicting undifferentiated small blue cells that need to be distinguished from other small blue cell tumors. We report an interesting case of DSRCT involving a pleural effusion with a “floating island” pattern that has been described in hepatocellular carcinoma, renal cell carcinoma, and adrenal cortical carcinoma. In our case, the epithelioid tumor cells form cohesive aggregates surrounded by a single layer of spindle cells, mimicking the “endothelial wrapping” in other tumors with “floating island” patterns. We demonstrate, by ancillary testing, that these peripheral spindle cells are tapered/flattened DSRCT cells, in contrast to endothelial wrapping cells, as seen in other tumors with this unique cytomorphology. To our knowledge, this is the first case report describing DSRCT showing a “floating island” pattern that needs to be differentiated from metastatic hepatocellular carcinoma, renal cell carcinoma, and adrenal cortical carcinoma in effusion cytology.